Future Development of Raw Material Policy Based on Statistical Data Analysis - Lucia Domaracká; Damiana Šaffová; Katarína Čulková; Marcela Taušová; Barbara Kowal; Simona Matušková (Resources, 2025)
For the European Union in the field of raw material policy, it is primarily important to ensure reliable, seamless, and unrestricted access to raw materials in all EU countries. An important aspect in assessing the European Union’s raw material policy is a detailed analysis of selected significant raw materials. This paper focuses on raw material policy within the European Union (EU). Specifically, it examines five types of raw materials: critical raw materials, metal ores, non-metallic minerals, fossil energy materials, and biomass. The research is oriented to analyzing the materials from the perspectives of consumption, mining, export, and import. The objective is to assess the European Union’s (EU) raw material policy by employing specific tools and statistical methodologies to analyze individual data. We aimed to assess the European Union (EU) raw material policy using selected statistical methods such as regression and correlation analysis, multivariate analysis, and pairwise correlation to reveal and describe the relationships between variables. Based on the examination of import and export data, it is evident that imports are on the rise while exports are declining. This trend underscores the EU’s continued reliance on raw materials sourced from other global regions. The results show that domestic production and consumption are sufficient; on the other hand, the EU remains dependent on imports of critical raw materials. The results are useful for the development of future EU raw material policy.